Dinamika Ontologi dan Epistemologi dalam realitas digital Integrasi Metaverse, Posthumanisme, dan Transhumanisme - Maimanah Angkat; Ahmad Yunus Mokoginta Harahap Ahmad Yunus Mokoginta Harahap (Jurnal Pendidikan Agama Islam, 2026)
The development of digital technologies, particularly the metaverse, artificial intelligence, and virtual reality, has triggered a fundamental transformation in the way humans understand reality, knowledge, and existence. This study aims to examine the dynamics of ontology and epistemology within digital reality through the integration of posthumanist and transhumanist perspectives, as well as through a theoretical synthesis of the approaches proposed by Popper, Kuhn, and Bhaskar. The study employs a qualitative research design based on library research using a systematic literature review approach of various reputable academic sources. The analysis was conducted through stages of content analysis, critical analysis, and conceptual synthesis. The findings reveal that digital reality constitutes a new form of ontology characterized as hybrid, relational, and constructive, which cannot be adequately explained through classical ontology grounded solely in materialism. In this context, digital epistemology demonstrates that knowledge is no longer acquired merely through empirical observation, but also through interaction within technologically mediated virtual environments. The integration of the theories of Popper, Kuhn, and Bhaskar produces a comprehensive analytical framework for understanding digital reality as a phenomenon that is simultaneously constructive and ontologically structured. Furthermore, this study confirms that posthumanism and transhumanism offer distinct yet complementary perspectives in explaining the transformation of human identity in the digital era. Posthumanism emphasizes the relationship between humans and technology, whereas transhumanism focuses on the enhancement of human capacities through technological advancement. This study proposes an integrative ontology–epistemology model which explains that digital reality and knowledge are simultaneously constructed through interactions between humans and technology. These findings contribute theoretically to the development of contemporary philosophy of science and open new avenues for further research in the fields of digital reality, artificial intelligence, and social transformation.